2020
DOI: 10.52435/complete.v1i1.47
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption Data Analysis: Indonesia Perspective

Abstract: Energy consumption has been increasing affected by many factors such as population growth, energy price, etc. This paper utilizes data analysis to examine energy consumption data and its correlation the GDP growth, particularly in case of Indonesia. The data observed in this study comprises a record from 1961-2018. An exploratory data analysis was employed to comprehend the features of the data, while beforehand a pre-processing and testing were conducted to prepare the data. Data visualization was built then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…In general, energy consumption has a positive impact on Indonesia's economic growth. When the two are combined, both make a positive contribution to the national economy (Prastyabudi and Hafidz, 2020), energy consumption is dominated by energy produced from fossils, namely oil, coal, gas. Meanwhile, renewable energy has been used since the early 2000s with a big jump in solar energy consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In general, energy consumption has a positive impact on Indonesia's economic growth. When the two are combined, both make a positive contribution to the national economy (Prastyabudi and Hafidz, 2020), energy consumption is dominated by energy produced from fossils, namely oil, coal, gas. Meanwhile, renewable energy has been used since the early 2000s with a big jump in solar energy consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Despite hosting massive renewable energy sources [32][33][34], Indonesia requires substantial transformations of policies and practices for a just transition towards a low-carbon economy. Still, the country's energy consumption between 1961 and 2018 revealed that energy consumption, dominated by fossil fuels, did not have a significant long-term association with GDP growth [35]. In that sense, energy consumption in Indonesia mainly occurred in mere nonproductive activities.…”
Section: Introductionmentioning
confidence: 97%
“…It is a major global issue, affecting global threats like nuclear war, epidemics, ecological crises, demographics, and international terrorism [1]. Fossil energy sources have declined rapidly while their consumption has gradually increased [2]. The rise in energy consumption will continue to grow as the population increases [3].…”
Section: Introductionmentioning
confidence: 99%